Pendidikan Karakter Berbasis Kearifan Lokal Pada Kesenian Teureubang Gembrung Di Kampung Naga - Muhammad Dwieky Cahyadien; Mujahid; Hayati, Fitroh (Tamadduna: Jurnal Peradaban, 2025)
This study examines the integration of character values within the local wisdom of Teureubang Gembrung as part of education in Kampung Naga. More than just cultural expression, this tradition serves as a tool for character building, fostering religiosity, togetherness, respect for nature, and gratitude to God. The research aims to explore the role of Teureubang Gembrung in shaping individual character while identifying both supporting and inhibiting factors in its implementation.Employing a qualitative approach, the study gathers data through observation, in-depth interviews, and documentation. The analysis follows Miles and Huberman’s interactive model, encompassing data reduction, presentation, and inference. Findings indicate that Teureubang Gembrung significantly contributes to the moral and spiritual development of the Kampung Naga community. This research enhances studies on character education rooted in local wisdom and offers policy recommendations for cultural preservation. The insights provided may serve as valuable references for academics, education practitioners, and stakeholders seeking to develop culturally grounded character education models.